Cutaneous metastasis as a first sign of breast carcinoma - Amalik Sanae, Resident in Radiology (Radiology Case Reports, 2021)
Unlike visceral, lymphonodal or bone metastases, skin metastases are rare and their identification portends of a bad prognosis. They may appear as the first sign revealing the primary tumour, synchronous or developing late in the course of neglected primary cancer. We report a case of 86 year-old women witch belongs to this rare group of patients in whom cutaneous metastasis were identified before the primary cancer. This case showed the interest of biopsy and imaging in the confirmation of the diagnosis.